Data-based approach for feedback–feedforward controller design using closed-loop plant data. (September 2018) - Jeng, Jyh-Cheng; Ge, Guo-Ping
Abstract: Feedforward control of measurable disturbances is a useful complement to feedback control because feedforward control performs control actions before a disturbance response occurs in a process output. In contrast to the typical model-based design approach, a novel data-based method for designing both the feedback and feedforward controllers is presented in this paper. The controller design directly exploits closed-loop plant data and does not require an identification of process and disturbance models. A feedback proportional–integral–derivative controller and feedforward lead-lag compensator are sequentially designed on the basis of the closed-loop response data for a set-point change and for a disturbance input, respectively. Because the controller design process uses plant data integrals, the proposed method is robust against measurement noise. Moreover, the proposed design method can be applied to improve existing underperforming feedback and feedforward controllers using routine closed-loop operating data. Simulation studies demonstrated that the proposed method outperforms existing methods in designing a feedback–feedforward control system. Highlights: A data-based method for designing the combined feedback–feedforward control scheme. The controller design directly exploits closed-loop plant data without identifying models. The controller design is robust against noise and applicable to routine operating data. The proposed design method is more effective than the model-based design methods. Practical applications to a reactor process and a wastewater treatment plant.